2012
DOI: 10.3390/md10102208
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Protease Activities of Diazepinomicin from the Sponge-Associated Micromonospora Strain RV115

Abstract: Diazepinomicin is a dibenzodiazepine alkaloid with an unusual structure among the known microbial metabolites discovered so far. Diazepinomicin was isolated from the marine sponge-associated strain Micromonospora sp. RV115 and was identified by spectroscopic analysis and by comparison to literature data. In addition to its interesting preclinical broad-spectrum antitumor potential, we report here new antioxidant and anti-protease activities for this compound. Using the ferric reducing antioxidant power (FRAP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 36 publications
(38 reference statements)
2
50
0
Order By: Relevance
“…Abdelmohsen and colleagues reported that the dibenzodiazepine alkaloid diazepinomicin ( 81 ) isolated from a strain of Micromonospora sp. RV115 associated with the Croatian marine sponge Aplysina aerophoba showed activity against T. brucei trypmastigote forms and inhibited the parasite protease rhodesain [86]. Desoti and colleagues extended the pharmacology of (−)-elatol ( 82 ), a sesquiterpene isolated from the Brazilian red alga Laurencia dendroidea shown to affect trypomastigotes of T. cruzi , demonstrating that it induced initial depolarization of the parasite’s mitochondrial membrane, followed by an increase in superoxide generation, as well as loss of cell membrane and DNA integrity [87].…”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%
“…Abdelmohsen and colleagues reported that the dibenzodiazepine alkaloid diazepinomicin ( 81 ) isolated from a strain of Micromonospora sp. RV115 associated with the Croatian marine sponge Aplysina aerophoba showed activity against T. brucei trypmastigote forms and inhibited the parasite protease rhodesain [86]. Desoti and colleagues extended the pharmacology of (−)-elatol ( 82 ), a sesquiterpene isolated from the Brazilian red alga Laurencia dendroidea shown to affect trypomastigotes of T. cruzi , demonstrating that it induced initial depolarization of the parasite’s mitochondrial membrane, followed by an increase in superoxide generation, as well as loss of cell membrane and DNA integrity [87].…”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%
“…Antioxidants have been used to protect cells against ROS, and natural antioxidants have been investigated for their use as preventive and therapeutic agents in medicine [1517]. …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Biological activities such as antibacterial, antifungal, antiparasitic, antimalarial, immunomodulatory, anti-inflammatory, antioxidant and anticancer activities were reported from sponge-associated actinomycetes. [12][13][14][15][16] These bioactivities are mediated by diverse groups of chemical compounds including polyketides, alkaloids, peptides and terpenes. 14,15,[17][18][19] The compound SF2446A2, a naphthacene glycoside previously reported from soil-derived Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] These bioactivities are mediated by diverse groups of chemical compounds including polyketides, alkaloids, peptides and terpenes. 14,15,[17][18][19] The compound SF2446A2, a naphthacene glycoside previously reported from soil-derived Streptomyces sp. strain SF2446, was found to exhibit strong activity against Gram-positive bacteria and several mycoplasma strains including the macrolide-resistant strain Mycoplasma gallisepticum.…”
Section: Introductionmentioning
confidence: 99%